Potential biosecurity breaches in poultry farms: Presence of free-ranging mammals near laying-hen houses assessed through a camera-trap study - Giulia Graziosi; Caterina Lupini; Francesco Dalla Favera; Gabriella Martini; Geremia Dosa; Gloria Garavini; Giacomo Trevisani; Alessandro Mannelli; Elena Catelli (Veterinary and Animal Science)
Diligent application and implementation of biosecurity measures stand as the most effective measures to prevent disease transmission through direct or indirect interactions between poultry and free-ranging animals. Among these, free-ranging mammals can be hosts or disseminators of several pathogens relevant to poultry and of public health concern. Moreover, evidence of susceptibility to avian influenza virus infection in non-human mammals has raised questions about their potential role in the virus' epidemiology at the domestic animal-wildlife interface. Given this background, this study aimed to identify mammal species occurring near laying-hen houses and characterize the spatiotemporal patterns of these visits. Seven camera traps were deployed for a year-long period in three commercial poultry farms in a densely populated poultry area in Northern Italy. Various methods, including time series analysis and generalized linear models, were employed to analyze daily mammal visits. A total of 1,867 camera trap nights yielded 567 videos of seven species of wild mammals, and 1,866 videos showed domestic pet species (cats and dogs). Coypus (Myocastor coypus) and cats were the two mammals more frequently observed near poultry houses. For wild mammals, visits significantly increased at night, and slightly decreased during the spring season. Overall, the data hereby provided lay the groundwork for designing novel surveillance and intervention strategies to prevent cross-species disease transmission. Moreover, the utilization of visual evidence depicting free-ranging animals approaching poultry houses could assist health authorities in educating and raising awareness among stakeholders about potential risks of pathogen spillover.